Risk Assessment of Ancient Colonnades - Diamantopoulos, Spyridon; Fragiadakis, Michalis (Technical Annals, 2024)
The paper presents a novel methodology for the fragility assessment of ancient freestanding colonnades. The seismic response and the stability of these colonnades is compared with those of freestanding columns. The modelling of the structures is based on a simplified approach that can be implemented in a general-purpose seismic design software. Thus, time-consuming and/or complicated simulations are avoided. For the fragility assessment, the performance criteria and the methodology adopted are discussed in detail. The examples studied show the capacity of the proposed modelling to simulate ancient structures and to quickly provide accurately the fragility curves. The Engineering Demand Parameter is always the rotation of the column over its slenderness while different Intensity Measures are examined.